El blog como herramienta didáctica para desarrollar el pensamiento crítico en estudiantes de noveno grado de básica secundaria y docentes (2021)
This academic work proposes to promote the development of critical thinking for academic and personal life in ninth grade students of secondary school, through a digital material - a blog - which is designed with a series of tools that allows the development of certain skills of this competence. According to this, in the present work learning and teaching strategies typical of “Learning to learn” are explored, which involve an active role of the student and teacher. Critical thinking is imperative to redefine the social function of education and, in the future, transform society.